Implementation of Digital Career Guidance Through a Chatbot Based on the Smart-Method - Prohimi, Afwan Hariri Agus; Syihabudhin; Juariyah, Lohana; Gunawan, Ari; Syaifruddin, Afis Baghiz; Indriati, Nur (Global Writing Academica Researching & Publishing, 2025)
Structured and personalized career planning is a crucial need for Vocational High School students in the digital era, especially in preparing for the transition to higher education or the world of work. However, conventional career guidance services still face challenges in terms of reach, personalization, and effectiveness. This study aims to develop and implement a chatbot-based career journey system with a SMART-Method approach (Specific, Measurable, Achievable, Relevant, and Time-bound) to improve the effectiveness of high school students' career planning. The study used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and a mixed methods approach. The chatbot was developed using the Telegram platform and is equipped with key features such as an interest and talent assessment, a SMART-based career goal planning guide, major and profession recommendations, and progress achievement reminders. Implementation was carried out on 120 11th-grade students at SMK Al-. Evaluation results showed that 87% of students felt helped in developing more specific and realistic career plans, while 91% stated that the chatbot provided an interactive experience that encouraged self-reflection on personal potential and interests. From the perspective of guidance and counseling teachers, the chatbot was deemed effective as a tool for systematically and documented monitoring of student progress. The SMART approach in the chatbot system helped students develop measurable and relevant goals, while providing a deadline for achievement that encouraged them to act proactively. These findings indicate that the integration of chatbot-based digital technology with structured pedagogical principles can improve the quality of career guidance services in schools. This study recommends further development in the form of digital portfolio integration, career literacy training for teachers and students, and cross-sector collaboration to strengthen an adaptive and sustainable career planning ecosystem in secondary education settings.